Children and disasters : a practical guide to healing and recovery - Zubenko, Wendy N., 1962-; Capozzoli, Joseph, 1953- (Oxford University Press, 2002)
Today, one in three Americans will be affected by trauma, and the most vulnerable among these victims are children. Children and adolescents in our communities are exposed to disastrous and devastating events, including natural disasters, violence, accidents, and, most recently, terrorist attacks, that have a great impact on their emotional and physical well-being. Children in Disasters is a training manual and reference for those who provide psychological relief in the wake of disasters. The expert contributors offer guidance for helping children integrate their traumatic experiences, develop healthy coping skills, and restore a sense of safety.